ESTIMATION OF PREVALENCE OF ADVERSE GENOTYPES AND POLYMORPHIC ALLELES OF GENES-CANDIDATES OF ARTERIAL HYPERTENSION IN CHILDREN WITH ENDEMIC GOITER IN ZABAYKALSKY KRAI - G. I. Bisharova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
This study is devoted to study the prevalence of genotypes and polymorphic alleles of genes-candidates of arterial hypertension in children with endemic goiter (EZ) in the Zabaykalsky Krai. To identify the frequency of occurrence of adverse genotypes and alleles polymorphisms Gly16Arg ADRB2, Gln27Glu ADRB2 and Thr174Met gene AGT, as factors of risk of development of arterial hypertension, were examined 194 children aged 7-11 years with a diagnosis of endemic goiter. The frequency of mutant allele 16Gly genotype Gly16Arg associated with increased agonist-induced suppression of beta-2 adrenergic receptors has not been above (63,2 %) than in the group of healthy children (60,3 %) (p(j2) > 0.05). The frequency of allele Arg16 defining a greater degree of vasodilating effect, was 39.7 % and 36.8 %, respectively (p(x2) > 0.05). Thefrequency characteristics of alleles genotype Gln27Glu in group I were the following: wild type 27Glu 41 %, the mutant allele Gln27 59 %, in the control group 42,2 % (p(χ2) > 0.05) and 57.8 % (pfy2) > 0.05) respectively. The frequency of wild-type Thr174 genotype Thr174Met accounted for 85.3 % in group I and 86.2 % in the control group (p(x2) > 0.05) and the frequency of occurrence ofthe mutated allele 174Met 14.7 % in the group of children with diffuse nontoxic goiter and 13.8 % in healthy children, respectively (pCx2) > 0.05). Significant differences in the distribution of genotypes and alleles between groups are not identified, and the frequency characteristics were comparable with the prevalence in the population and the results of other authors. The distribution of genotypes and frequency of alleles of a gene Gly16Arg and Gln27Glu ADRB2, Thr174Metgene AGT in both groups corresponded to the expected according to the hardy-Weinberg equilibrium in the population sample. The results obtained in the course of molecular-genetic study led to the conclusion that polymorphisms Gly16Arg ADRB2, Gln27Glu ADRB2 and Thr174Met gene AGT are not factors of risk of development of arterial hypertension in children with endemic goiter.